AI-06 Dalazatide, an inhibitor of the kv1.3 channel on activated effector memory T cells, has immunotherapy potential against systemic lupus erythematosus. (31st August 2016) - Stevens, Anne; Yuasa, Megan; Peckham, David; Olsen, Chelsea; Iadonato, Shawn; Probst, Peter
Abstract : Background: T cell activation depends upon a calcium signalling cascade that is regulated by voltage-gated potassium channels. Effector memory T cells (TEM ), which are implicated in the immunopathogenesis of autoimmune diseases, express relatively high levels of the potassium channel Kv1.3. Dalazatide is a potent peptide inhibitor of the Kv1.3 channel that has recently shown safety and efficacy in a Phase 1 b plaque psoriasis trial. Evidence suggests that inflammatory cytokine producing TEM cells might be involved in the immunopathology of lupus nephritis. The objective of this study is to provide proof-of-principle ex vivo data for therapeutically targeting chronic T cell activation in systemic lupus erythematosus (SLE). Materials and methods: Peripheral blood mononuclear cells from paediatric and adult SLE patients as well as healthy controls were studied. T lymphocyte subsets were assayed ex vivo for Kv1.3 expression by flow cytometry. The effect of dalazatide on inflammatory cytokine expression by TEM cells activated by thapsigargin/phorbol myristate acetate (PMA) or ionomycin/PMA was evaluated by intracellular cytokine staining. Results: Kv1.3 expression by CD8 + TEM cells was significantly higher in patients with active lupus nephritis when compared to patients with inactive SLE or healthy controls. Dalazatide inhibited IFN-γ, IL-17 and TNF-α production by both CD4 + and CD8 + TEM cells from SLE patients in a dose-dependent manner. Dalazatide-mediated inhibition was more significant in IFN-γ and TNF-α-expressing CD4 + TEM cells from patients with active SLE compared to cells from patients with inactive disease. Conclusions: Ex vivo studies suggest that dalazatide inhibition of Kv1.3 on TEM may be an effective strategy for treating SLE. In addition, Kv1.3 expression may be a useful biomarker of SLE disease activity.